Pengaruh Perbedaan Konsentrasi Emulgator terhadap Karakterisasi Fisik Sediaan Krim Ekstrak Rosella (Hibiscus sabdariffa) - Ike Widyaningrum; Sasi Purwanti (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
The formulation and physical characterization test of rosella extract cream preparations have been carried out using various types of non-ionic emulsifier concentration ratios (combination of tween 80 and span 80). Comparison of the concentrations of tween 80 and span 80 used in this study were 2%, 3%, and 4%. The aim of this study included organoleptic test, homogeneity test, pH test, viscosity test, dispersion test, and emulsion type test. The result obtained from the physical characterization test were the organoleptic tests for the three formulas showed the same organoleptic results, namely red color, characteristic smell of rosella, and semisolid consistency. Homogeinity test shows that the formula is homogenous. The pH test showed that F1 4,29; F2 4,6; F3 5. Viscosity test showed that F1 432,4 mPas; F2 434,3 mPas; 435,3 mPas. The dispersion test was carried out without using a load of 50 g, 100 g, and 200 g. the results shown form the spreadability test of three formulas were were F1 5 cm; 5,5 cm; and 6 cm; F2 6 cm; 6,35 cm; 7,25; and 7,5 cm. F3 6,25 cm; 7,5 cm; 7,75 cm; 8 cm. The emulsion type indicated by the three formulas is oil in water. Based on these results, it can be seen that the emulsifier concentration has an effect on PH, viscosity, and spreadibility. The higher the concentration of emulsifier used, the higher pH value, viscosity, and spreadibility.